IMPLEMENTATION OF IOT-BASED SMART MEDICINE BOXES TO IMPROVE MEDICATION COMPLIANCE AND PUBLIC HEALTH LITERACY IN PALASARI VILLAGE, CIBIRU DISTRICT - Hakim, Nurul Fahmi Arief; Al Azhima, Silmi Ath Thahirah; Darmawati, Irma; Al Qibtiya, Mariya; Hartopo, Ibnu; Ridwan , Azwar Mudzakkir (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Improving patient safety through proper drug management is particularly difficult for the elderly and people with chronic conditions. Due to low levels of health literacy and lack of access to health technology, numerous individuals in Palasari Village, Cibiru District still struggle to adhere to prescription schedules. As a technical solution to aid in appropriate medication administration, this community service research proposes an IoT-based smart medicine box. A community needs analysis, a prototype built on an ESP32 microcontroller, a dose detection sensor, and a notification system using a mobile app were all part of the implementation technique. Residents also participated in training and mentorship sessions. The trial included 27 participants who were evaluated using a Likert scale that measured their level of interest, comprehension, simplicity of use, and effectiveness with respect to the gadget. With an average score of 4.37 out of 5 (87.3%), the results demonstrated a high degree of acceptability, especially when it came to comprehending the gadget, the efficacy of medicine reminders, and the possibility of lowering the risk of medication mistakes. At the community level, this effort proves that basic technology based on the Internet of Things may enhance health literacy, patient safety, and medication adherence.